Green's Second Identity for Vector Fields. (6th August 2012) - Fernández-Guasti, M.
Abstract : The second derivative of two vector functions is related to the divergence of the vector functions with first order operators. Namely, P · ∇ 2 Q - Q · ∇ 2 P = ∇ · [ P ( ∇ · Q ) - Q ( ∇ · P ) + P × ∇ × Q - Q × ∇ × P ] .